A belt for the cell: cellulosic wall thickenings and their role in morphogenesis of the 3D puzzle cells in walnut shells. (8th May 2021) - Antreich, Sebastian J; Xiao, Nannan; Huss, Jessica C; Gierlinger, Notburga
Abstract : We show the development of the 3D puzzle sclereids, which make up the whole walnut shell, and discuss the potential role of cell wall thickenings during tissue morphogenesis. Abstract: Walnut ( Juglans regia ) kernels are protected by a tough shell consisting of polylobate sclereids that interlock into a 3D puzzle. The shape transformations from isodiametric to lobed cells is well documented for 2D pavement cells, but not for 3D puzzle sclereids. Here, we study the morphogenesis of these cells by using a combination of different imaging techniques. Serial face-microtomy enabled us to reconstruct tissue growth of whole walnut fruits in 3D, and serial block face-scanning electron microscopy exposed cell shapes and their transformation in 3D during shell tissue development. In combination with Raman and fluorescence microscopy, we revealed multiple loops of cellulosic thickenings in cell walls, acting as stiff restrictions during cell growth and leading to the lobed cell shape. Our findings contribute to a better understanding of the 3D shape transformation of polylobate sclereids and the role of pectin and cellulose within this process.